Mononuclear Transition Metal Complexes Containing Quadridentate Schiff Bases as N2O2 Donors: Synthesis, Spectral Characterization Properties and Antibacterial Activity - Kumar, D. Sathis; Gandhi, S. Rajiv; Mageswari, Anbazhagan; Karthikeyan, Sivashanmugam; Sheriff, A.K. Ibrahim (Asian Journal of Chemistry, 2015)
A qudridendate Schiff base ligand is synthesized by the condensation of active primary amine 2-amino-4-tert-butylphenol with b-diketone. It is found to be an N2O2 donor chelate. Quadridentate Schiff bases with an N2O2 donor have been widely studied for their ability to coordinate metal ions. Its complexes with Fe(III), Co(II), Ni(II), Cu(II) and Zn(II), have been synthesized and characterized by micro analysis, molar conductivity, magnetic susceptibility studies, UV, IR, NMR, Mass spectral studies, cyclic voltammetry, ESR spectral studies, thermal behaviour and Powder X-ray diffraction studies have also been carried out. The DNA cleavage activities of the Schiff base and its complexes were monitored by agarose gel electrophoresis method in the presence of hydrogen peroxide and antibacterial activities have also been studied.